Government Shutdown and SNAP Disbursements: Effects on Household Expenditures - Mindy Marks; Silvia Prina; Roy Gernhardt (Institute of Labor Economics (IZA), 2023)
We test the ability of SNAP eligible households to smooth consumption when facing unexpected transitory income shocks stemming from the 2018-19 government shutdown. In response to the shutdown, all states were federally mandated to pay February SNAP benefits on or before January 20th. This created a short-term windfall (two payments very close to each other) followed by a longer than normal gap during which no SNAP disbursements were received. We show that expenditures are lower in the month where benefits where advanced vis-à-vis months with unaltered benefits schedules. We complement this finding by exploiting preexisting state-level differences in disbursement schedules that drove some states to temporarily alter the timing of the 2019 March and April SNAP disbursements. These diff-in-diff results show that households in treated states reduced spending when there was a longer than usual gap between SNAP disbursements. Our findings are inconsistent with the permanent income hypothesis.
Keywords: D12; I3; I38; 330; consumption smoothing; permanent income hypothesis; SNAP; government shutdown